Acute poisoning in children; Evaluation of cases admitted to Marmara University Hospital in 2015 - İNANICI, MEHMET AKİF; TIPLAMAZ, SITKI (MARMARA UNIV, FAC MEDICINE, 2018)
Objectives: According to Turkish Statistical Institute (TurkStat), 6477 children aged between 1 and 17 years, died in 2015 and 29.5% (n=1909) of these deaths were because of injuries due to external causes and poisoning. Our aim is to produce solutions to this problem by evaluating demographics, clinical features of patients and the causes and consequences of poisoning. Materials and Methods: The hospital medical records of children who were admitted with acute intoxication to Pediatric Emergency Service at Marmara University Hospital in 2015, were evaluated retrospectively. Results: In 2015, a total of 1110 patients applied to the hospital due to poisoning. Of these cases, 31.6% (n = 351) were children, about half of them were male (n = 173) and half were female (n = 178). The mean age of males was 6.24 years and mean age of females was 8.47 years. Sixty percent (n=213) of patients were in 0-6 age group, 8% (n=28) of patients were in 7-11 age group, 32 % (n=110) of patients were in 12-18 age group. Forty-six point one percent (n = 162) were poisoned with medications. Among the pharmaceuticals, paracetamol was the most commonly used agent (14.8%). In non-pharmaceuticals, caustic/corrosive substances (detergent, bleach, acetone etc.) were the most frequently used agents (54%). Conclusion: In this study, 80.3% of the cases were preventable accidental poisoning. Regulations on child-resistant packaging should come into force as soon as possible.
Keywords: Forensic origin; Child; Intoxication; CHILDHOOD; ABUSE